(untitled) (Ustozlar uchun, 2025)
This article examines the significant achievements of Uzbekistan’s youth in recent years (2023–2025) across education, innovation, entrepreneurship, sports, and culture. It analyzes these successes within the framework of the “Uzbekistan-2030” strategy and state youth policy. Based on official statistics and formal sources, the article highlights the role of young people in building a New Uzbekistan and outlines future prospects for the nation’s “golden generation.”